STRATEGI PENYELAMATAN ARSIP STATIS PANDEMI COVID-19 SEBAGAI MEMORI KOLEKTIF BANGSA OLEH LEMBAGA KEARSIPAN: Array - Azmi Azmi (Jurnal Kearsipan, 2020)
The phenomenon of political, social, economic, and cultural life in Indonesia in the figth against the pandemic COVID-19 leaves historical records in various forms and media (paper, maps, pictures, infographics, photos, audio, video, and digital) called COVID-19 pandemic archives. The COVID-19 pandemic archives is crucial for historical evidence, sources of knowledge, continuous innovation, and material for national liability for the life of society, nation and state. The archival institution as a static archival management institution in Indonesia as mandated Law of Number of 43 of 2009 on Archival has the responsibility of saving the COVID-19 pandemic archives produced by state institutions, regional governments, companies, political organizations, social organizations, and individuals as nation's collective memory. The study of saving the COVID-19 pandemic archives aims to examine the problem of the right strategy for archival institutions in saving the COVID-19 pandemic archives as the nation's collective memory. The analysis result showed that the strategy of saving the COVID-19 pandemic archives as a collective memory was carried out through policy making, applying strategic acquisition methods and documentation strategies, optimizing resources, and increasing COVID-19 pandemic archives access.